Visual Arts in Early Childhood Education and Elementary School: Repainting the school space with children from the Novo Oriente community, in Maracanaú/CE (Revista Apotheke, 2025)
This is an experience report from the researchers of the Project Repainting the school space with children from the Novo Oriente community, in Maracanaú/CE, supported by the XII Public Notice for Incentive to the Arts from the Department of Culture of the State of Ceará, held in the first half of 2023, in partnership with the Municipal School of Early Childhood and Elementary Education Maestro Eleazar de Carvalho. The project consisted of holding workshops/ateliers in Visual Arts, which resulted in the construction of two children's books based on the their narratives, drawings, paintings and graffiti. It was considered that - in addition to social and affective-emotional vulnerabilities -, upon returning to school, in the midst of the post-pandemic scenario and the socioeconomic compromise of their families, many of these children were significantly harmed in the development of their basic social and educational skills. We conclude with this project that it is possible to (re)integrate these children, from 05 (five) to 07 (seven) years of age, in moments of training with Visual Arts, providing them with experiences on recognizing differences and respecting diversity, as well as better opportunities for learning and school socialization. Experiences with children's literature, drawings and graffiti/murals also allowed us to perceive children as integral beings, with diverse and complex biological, psychological, social, emotional and cultural aspects, which must be jointly and properly enhanced for development. of their cognitive, artistic and community skills.
Keywords: visual arts; children; childhood and early years education; school in the post-pandemic context; Maracanaú/CE